2008
DOI: 10.1002/bit.22122
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of a foamed emulsion bioreactor: II. model parametric sensitivity

Abstract: The sensitivity of a conceptual model of a foam emulsion bioreactor (FEBR) used for the control of toluene vapors in air was examined. Model parametric sensitivity studies showed which parameters affect the removal of toluene (as model pollutant) in the FEBR the most significantly, and enabled definition of the limits of the process. Detailed examination of the results indicated that the process is highly complex and that both mass transfer and kinetic limitations can coexist in the bioreactor system. These re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Simulations indicated that most of the toluene is removed near the gas-liquid interface, and that biodegradation is the principal mechanism for pollutant removal. Further studies of the model presented in the companion paper (Kan and Deshusses, 2008) provide insights on the model parametric sensitivity and on the performance limits of the FEBR process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Simulations indicated that most of the toluene is removed near the gas-liquid interface, and that biodegradation is the principal mechanism for pollutant removal. Further studies of the model presented in the companion paper (Kan and Deshusses, 2008) provide insights on the model parametric sensitivity and on the performance limits of the FEBR process.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, a conceptual model that describes toluene (as a model pollutant) degradation in FEBRs is presented and validated with experimental results. Model parametric sensitivity studies are presented and discussed in the companion paper (Kan and Deshusses, 2008).…”
Section: Introductionmentioning
confidence: 99%